Respuesta :

sid071

Hey there!!

Given equation :

... 4x +3(x+2) = 5(2x-3)

Using the distributive property :

... 4x + 3(x) + 3 (2) = 5(2x) + 5(-3)

... 4x + 3x + 6 = 10x - 15

Combining the like terms :

... 7x + 6 = 10x - 15

Subtracting 7x on both sides :

... 6 = 3x - 15

Adding 15 on both sides :

... 21 = 3x

Dividing by 3 on both sides :

... x = 7

This is the solved equation. The first step we have done to solve the equation was using the distributive property.

Hope my answer helps!